The contribution of credit accumulation and transfer system: Lessons to the Ethiopian national qualifications framework - Abebaw Yirga Adamu (College of education, Bahir Dar University, 2023)
Ethiopia is a developing country which aspires to become a middle income country by 2025. To realize this vision different development plans including the Growth and Transformation Plan and the Plan for Accelerated and Sustained Development to End Poverty have been developed. The first step toward supporting development plans through education is developing education and training policies, strategies and devices that aim to improve the knowledge, skills and competence of the society. In relation to this one of the instruments which have been used in several countries to enhance quality of education, promote recognition of qualifications and facilitate lifelong learning is National Qualifications Framework. This paper argues that, among others, well-designed and implemented credit accumulation and transfer system could support the Ethiopian National Qualifications Framework in achieving its purposes by facilitating quality assurance, recognition of prior learning, progression and transfer between institutions and education sectors, mobility and comparability and recognition of qualifications both at national and international levels